Trends in Antidepressants Use in Spain between 2015 and 2018: Analyses from a Population-Based Registry Study with Reference to Driving - Eduardo Gutiérrez-Abejón; Francisco Herrera-Gómez; Paloma Criado-Espegel; F. Javier Álvarez (MDPI AG, 2020)
Antidepressants are considered driving-impairing medicines (DIM). This is a population-based registry study that shows the trend in the use of antidepressants in Castile and León, Spain, from 2015 to 2018. Data on antidepressant dispensations at pharmacies and the adjusted use of these medicines by the driver population are presented. For the purposes of analysis, population distribution by age and gender has been taken into account, as well as the three Driving Under the Influence of Drugs, alcohol, and medicines (DRUID) categories. Antidepressants were used by 8.56% of the general population and 5.66% of drivers. Antidepressants were used more commonly by females than by males (12.12% vs. 4.87%, χ² = 1325.124, p = 0.001), and users increased as the age increased, even if women who drive used less antidepressants after turning 60 years of age. Chronic use of antidepressants was relevant (8.28%) in the same way as daily use (3.15%). Most of the consumption included SSRIs (4.99%), which are also known as "other antidepressants" (3.71%). Regardless of antidepressants consumed, users took 2.75 ± 1.19 DIMs, which are mainly anxiolytics (58.80%) and opioids (26.43%). Lastly, regarding consumption of antidepressants according to the DRUID classification, category I predominated over categories II and III. Our findings should serve as a starting point for health and traffic authorities to raise awareness of the risk for traffic accidents, especially involving SSRIs.